Phonological Variation Technology Integration for Indonesia Cultural Preservation and Edupreneurship - Hetilaniar, Hetilaniar; Zulaeha, Ida; Mardikantoro, Hari Bakti; Yuniawan, Tommi; Lachlan, Nicholas (Pandawan, 2025)
This study explores phonological variations in the Komering dialects of South Sumatra, Indonesia, examining differences in vowel and consonant phonemes influenced by geographical and socio-cultural factors. Using a descriptive qualitative approach and synchronic dialectology, data were collected through field observations, in-depth interviews, and technological tools like Praat software and Natural Language Processing (NLP). The findings reveal significant phoneme shifts, such as [i] to [ε] and [h] to omission. Despite these variations, the linguistic kinship among Komering dialects remains strong, reflecting community interactions and adaptations. This research emphasizes the importance of preserving endangered regional languages by integrating phonological research with educational technology and gamification, aligning with Sustainable Development Goals (SDG 4: Quality Education and SDG 10: Reduced Inequalities). Proposed solutions include interactive language learning tools and edupreneurship initiatives to engage younger generations while fostering cultural preservation and creative innovation. The study contributes to linguistic understanding, cultural heritage preservation, and inclusive education by offering sustainable approaches to address language endangerment in the digital age.